Induction chemotherapy in patients with resectable head and neck squamous cell carcinoma: a meta-analysis - Ma, Jie (BioMed Central, 2013)
BACKGROUND: Induction chemotherapy has been investigated as a possible strategy to shrink or downstage locally advanced head and neck cancers, providing opportunity to remove the lesions completely after induction chemotherapy, especially in the patients with resectable advanced disease. The aim of this study was to investigate the definitive effect of induction chemotherapy in patients with resectable head and neck squamous cell carcinoma. METHODS: A meta-analysis of randomized trials (1965–2011) was performed on the impact of induction chemotherapy on survival, disease control, and toxicity in this population of patients. Kaplan-Meier curves were read by Engauge-Digitizer. Data combining was performed using RevMan. RESULTS: Fourteen trials (2099 patients) were involved in this analysis. There was no significant difference on overall survival, disease free survival, or locoregional recurrence between the patients treated with and without induction chemotherapy (P >0.05). However, the patients treated with induction chemotherapy had a lower rate of distant metastasis by 8% (95% confidence interval 1%–16%, P = 0.02) than those treated without induction chemotherapy. In patients with laryngeal cancer, comparing to radical surgery, the larynx could be preserved in responders to induction chemotherapy without survival decease (P >0.05). Induction chemotherapy-associated death was 0%–5%. CONCLUSIONS: Based on the results above, there is a significant benefit of induction chemotherapy on decreasing distant metastasis in patients with resectable head and neck squamous cell carcinoma. In patients with laryngeal cancer, induction chemotherapy provides larynx preservation in responders to induction chemotherapy.